Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Cumulative Review - Page 481: 47



Work Step by Step

6$x^{2}$-2x-20=6$x^{2}$-12x+10x-20=6x(x-2)+10(x-2)= =(6x+10)(x-2)=2(3x+5)(x-2)
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.